The rural private practitioner - Rohde, Jon E.; Viswanathan, Hema. (Delhi : Oxford University Press, 1995)
Study of the rural private practitioners in India.
Bibliography: (p. 155-159).
Keywords: Medicine, Rural -- Practice -- India